Isolation and In Silico Anti-SARS-CoV-2 Papain-Like Protease Potentialities of Two Rare 2-Phenoxychromone Derivatives from Artemisia spp - Suleimen, Y.M.; Jose, R.A>; Suleimen, R.N.; Arenz, Ch.; Ishmuratova, M.; Toppet, S.; Dehaen, W.; Alsfouk, A.A.; Elkaeed, E.B.; Eissa, I.H.; Metwaly, A.M. (Molecules, 2022)
Two rare 2-phenoxychromone derivatives, 6-demethoxy-4‘-O-capillarsine (1) and tenuflorin C (2), were isolated from the areal parts of Artemisia commutata and A. glauca, respectively, for the first time. Being rare in nature, the inhibition potentialities of 1 and 2 against SARS-CoV-2 was investigated using multistage in silico techniques. At first, molecular similarity and fingerprint studies were conducted for 1 and 2 against co-crystallized ligands of eight different COVID-19 enzymes. The carried-out studies indicated the similarity of 1 and 2 with TTT, the co-crystallized ligand of COVID-19 Papain-Like Protease (PLP), (PDB ID: 3E9S). Therefore, molecular docking studies of 1 and 2 against the PLP were carried out and revealed correct binding inside the active site exhibiting binding energies of 􀀀18.86 and 􀀀18.37 Kcal/mol, respectively. Further, in silico ADMET in addition to toxicity evaluation of 1 and 2 against seven models indicated the general safety and the likeness of 1 and 2 to be drugs. Lastly, to authenticate the binding and to investigate the thermodynamic characters, molecular dynamics (MD) simulation studies were conducted on 1 and PLP.
Keywords: Artemisia commutate; 2-phenoxychromones; SARS-CoV-2; COVID-19 Papain-Like Protease; molecular docking; molecular fingerprints; ADMET; MD simulations